Bursa Efek dalam Perspektif Islam - Duwi Lismawati; Nurma Wahyu Lestari; Mochammad Miftahul Hakim; Mohammad Asrori (EduInovasi: Journal of Basic Educational Studies, 2024)
The term "buying and selling transactions with goods" has been heard by many people and has now developed very rapidly. Even carrying out buying and selling transactions abroad. In addition, buying and selling transactions in the form of money are increasing every year. People are more interested in investing in a company or institution that is equivalent to using the assets they own through capital market intermediaries. At the time of Rasulullah SAW, the name stock exchange had never been heard of. Seeing this does not mean it is haram. Therefore, there are still many scholars who disagree about this matter.